Information technology of developing test kits based on software requirements - Lysenko, I.; Smirnov, A. (IJCER, 2016)
The article presents an advanced information technology of developing test kits based on software requirements using regulated cascading decision charts, providing the increase of coverage completeness by the projected test kits of software requirements and the accuracy of the tests themselves. The article presents an advanced information technology of developing test kits based on software requirements using regulated cascading decision charts, providing the increase of coverage completeness by the projected test kits of software requirements and the accuracy of the tests themselves.
Keywords: information technology; software; testing; development; test kit; decision chart